Appraisal Theory and Interpreting Political Speech - Mohammed, Alhuthali (European Scientific Journal, ESJ, 2024)
Appraisal Theory can be used to study the semiotic content of formal speeches. This paper suggests there are important differences in the modes used at different stages as a speech shifts overall tone or purpose. While Affect is common across the speech structure, Judgement is more commonly found in sections that can be seen as instances of expected politeness towards the intended audience. By using such modes, the speaker is effectively inviting agreement with their overall presentation. For this paper, two speeches by Ban Ki Moon were studied. The first in 2006 is his acceptance speech and the second, in 2016, on leaving his role as Secretary General of the United Nations.